2014
DOI: 10.1016/j.jadohealth.2013.11.008
|View full text |Cite
|
Sign up to set email alerts
|

The Health and Well-Being of Transgender High School Students: Results From the New Zealand Adolescent Health Survey (Youth'12)

Abstract: This is the first nationally representative survey to report the health and well-being of students who report being transgender. We found that transgender students and those reporting not being sure are a numerically small but important group. Transgender students are diverse and are represented across demographic variables, including their sexual attractions. Transgender youth face considerable health and well-being disparities. It is important to address the challenging environments these students face and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
333
4
27

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 453 publications
(419 citation statements)
references
References 19 publications
25
333
4
27
Order By: Relevance
“…Somewhere between 2% and 3% of school-aged children both "behave like the opposite sex" and "wish to be the opposite sex" with regular frequency (Van Beijsterveldt, Hudziak, & Boomsma, 2006;see Zucker & Lawrence, 2009, for a review), suggesting that an unexpected "mismatch" between sex and gender likely occurs within nearly one in every two classrooms. And a recent representative study of New Zealander high school students showed that 1.2% of them identified as transgender, with 94.7% identifying as nontransgender (the remainder was unsure or did not understand the question; Clark et al, 2014). Depending on the specific definition one uses of intersex, these children are also more common than many believe as they represent 0.02% to 1.7% of children (Ainsworth, 2015;Fausto-Sterling, 1993;Sax, 2002).…”
Section: Beyond Discrete Categories: the Cases Of Gender And Sexmentioning
confidence: 99%
“…Somewhere between 2% and 3% of school-aged children both "behave like the opposite sex" and "wish to be the opposite sex" with regular frequency (Van Beijsterveldt, Hudziak, & Boomsma, 2006;see Zucker & Lawrence, 2009, for a review), suggesting that an unexpected "mismatch" between sex and gender likely occurs within nearly one in every two classrooms. And a recent representative study of New Zealander high school students showed that 1.2% of them identified as transgender, with 94.7% identifying as nontransgender (the remainder was unsure or did not understand the question; Clark et al, 2014). Depending on the specific definition one uses of intersex, these children are also more common than many believe as they represent 0.02% to 1.7% of children (Ainsworth, 2015;Fausto-Sterling, 1993;Sax, 2002).…”
Section: Beyond Discrete Categories: the Cases Of Gender And Sexmentioning
confidence: 99%
“…One of the first population-based studies estimated that 1.2% of high school students identified as transgender, with 2.5% 'not sure' of their gender 5 . Sexual and gender minority youth have been reported to have at least 1.5 times the rates of depression, suicidality and elevated rates of other mental health problems than their heterosexual or nontransgender (cisgender) peers [5][6][7][8] . This phenomenon may be due to disproportionate 'minority stress' from heteronormative (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…heterosexuality is the only 'normal' or acceptable sexual orientation) and cis-normative (i.e. the assumption that all people are cisgender and/or should be cisgender) challenging environments and discrimination 4,5,9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…The secretariat struggled long to get records from the NBTS. Those records operated with much smaller numbers that what have been found in recent international statistics, where the prevalence of self-declared transgender is around 1% [7]. This prevalence greatly exceeds the basis for the present centralization and monopolization.…”
Section: Some Of What Caused Extra Debate In the Proceedingsmentioning
confidence: 81%